"Good education” and its instrumental description in the narrations of adults who have become students - Jurgiel-Aleksander, Alicja (Adult Education Discourses, 2020)
The author of this article argues that the problem of good education is a public issue. Inspired by theorist G.J.J. Biesta who posed questions regarding the significance of good education, the author interviewed adult students about this phenomenon. The phenomenographic analyses of students’ statements unveiled three description categories of good education. These are: good education as a synonym of the school which fulfils standards of teaching, good education as an instrument of human success and good education as a tool of human enlightening. All the students’ descriptions led to the observation that the common horizon of the understanding of good education was the idea of education as a method which is goal oriented. This means that good education is described here through the prism of concrete aims and effective tools, but not by means of problematic ideas and values which serve these goals. This attitude may result in instrumental relations between people and the world, and the quality of the (worse) human condition.